Investigating the underlying mechanisms of the ethanol extract of saussureae involucratae herba in anti-rheumatoid arthritis effect based on sphingolipidomics - Chi, Pingyuan; Zhang, Hairong; Chen, Yingjie; Xie, Jianhua; Ayixianmuguli, Yiming; Wu, Caisheng; Liu, Mingyuan (Frontiers in Pharmacology, 2025)
IntroductionSaussureae Involucratae Herba (SIH), a traditional Chinese Medicine, is clinically used in treating rheumatoid arthritis (RA). However, the anti-RA mechanisms of SIH remain unclear. Dysregulation of sphingolipid metabolism is related to the pathogenesis of RA. This study aims to investigate whether the regulation of sphingolipid metabolism is involved in the anti-RA effects of an ethanol extract of SIH (SIE).MethodsThe collagen-induced arthritis (CIA) mouse model and LPS-stimulated RAW 264.7 cells were used. Targeted sphingolipidomics were employed to investigate the effects of SIE on the regulation of sphingolipid metabolism in CIA mice.ResultsResults showed that SIE significantly reduced arthritis scores and the average thickness of the four paws (both P < 0.01) in CIA mice. Additionally, it improved histopathological manifestations (including synovial hyperplasia, inflammatory cell infiltration, cartilage and bone destruction) in the ankle joints of CIA mice, and inhibited bone erosion in the ankle and toe joints. In cell assays, SIE significantly decreased the protein levels of TNF-α and IL-6 (both P < 0.01) in LPS-stimulated RAW 264.7 cells. Mechanistically, SIE treatment normalized the concentration of seven sphingolipids in plasma and eight sphingolipids in spleen, which were identified as potential anti-RA targets of SIE. Meanwhile, SIE treatment significantly lowered the protein level of SphK1 and the content of S1P (both P < 0.01) in LPS-stimulated RAW 264.7 cells.DiscussionWe, for the first time, found that SIE has anti-RA effects in CIA mice and that regulation of sphingolipid metabolism is involved in its anti-RA action. These findings provide pharmacological evidence for the use of SIH in managing RA and support the theory that targeting sphingolipid metabolism is a strategy for treating RA.